Visualizing climate activism on social media - Shim, David (Käte Hamburger Kolleg/Centre for Global Cooperation Research (KHK/GCR21), 2023)
This paper examines the visual dimension of climate activism by exploring how Fridays for Future Germany (FFFG) uses visual imagery to convey the politics of climate change to wider audiences. The author argues that FFFG is an ideal-type form of visual activism in which visual imagery is central to its climate activism. The paper builds on climate change communication scholarship and visual social movement studies to contribute an inquiry about FFFG's visual activism. The focus is on FFFG's visual self-representations, which promises to give insights into its strategies of self-legitimation. The empirical analysis identifies recurring visual patterns in FFFG's visual activism and provides an interpretive reading about the implications of certain ways of seeing and showing climate change. The conclusion puts the findings in a wider political context, highlighting the importance of visualization in the (self-)legitimation of FFFG in debates about global climate governance.
urn:nbn:de:hbz:465-20230510-090914-7
Keywords: Graue Literatur; Fridays for Future; visual activism; climate change communication; environmental communication; social movements; imaginaries/narratives; visibility